Correlation between oil and coal price with electricity tariff : a study of Tenaga Nasional Berhad / Nursafuraa Redzali - Redzali, Nursafuraa (Faculty of Business and Management, 2011)
Currently, as a result of global price escalation of coal and fuel/gas, TNB faced a challenging time dealing with increased operational costs as well as managing the existing high debt to support its daily operations. Because of these high borrowings, TNB was exposed to excessive financial risks in particular foreign currency risk since the borrowings were mostly denominated in foreign currencies. This high borrowing had resulted in an unstable credit ratings made by domestic and international rating agencies which might affect the perception of local and foreign investors as well as the financial institutions towards the company. In addition, single customer limit was also one of the reasons why TNB had to commit foreign currencies borrowing. Other main constraints included among others security of coal supply and uncertainty in coal pricing which severely impacted TNB’s cash flows in addition to generating electricity for the nation. Due to these overriding constraints, few alternative solutions were proposed and analysed in order to mitigate the problems. Among the solutions proposed were (i)TNB to establish policies to minimise financial risk such as credit risk policy, interest rate risk policy, liquidity risk policy, foreign exchange risk policy and permitted instruments policy; (ii) TNB must strive in the future to secure borrowing in Ringgit Malaysia which seem to be a least cost financing and (iii) few alternative solutions were proposed to overcome coal supply security and price uncertainty.